Structure and environmental drivers of an abyssal-hadal scavenging amphipod assemblage - Jennifer A. Wainwright; Denise J.B. Swanborn; Elin A. Thomas; Devin Harrison; Johanna N.J. Weston; Alan J. Jamieson (Progress in Oceanography, 2026)

Bottom mixed layer derivation and spatial variability over the central and eastern abyssal Pacific Ocean - Jessica Kolbusz; Devin Harrison; Nicole Jones; Joanne O'Callaghan; Taimoor Sohail; Todd Bond; Heather Stewart; Alan Jamieson (Ocean Science, 2026)
The bottom mixed layer (BML) of the abyssal ocean regulates heat exchange between the deep interior and seafloor, driving water–mass transformation and influencing global circulation. Spatial variability of the BML was examined in the under-sampled abyssal Pacific Ocean using surface-to-seafloor temperature and pressure observations over 4 months in 2023–2024. Given the typical decadal repeat rate of global hydrographic sections, subdecadal variability in the abyssal ocean has remained poorly resolved. Our observations contribute towards filling this gap for the central and eastern abyssal Pacific Ocean. Four methods were used to determine the BML thickness, with the threshold method providing the most reliable estimates. The mean BML thickness was (226 ± 172 m) with added repeat hydrographic sections providing context and additional data points. At each BML data point we determined the slope, the terrain roughness and the extracted predicted internal tide energy dissipation (over five different low-mode processes and high-mode local processes) at 50 km scales from publicly available datasets. These factors were input into a Random Forest Regressor (RF) model, the first time machine learning techniques have been applied to investigate BML thickness. The RF feature importance scores identified bottom depth, total internal tide energy dissipation, followed by slope, as the strongest predictors of BML thickness, revealing the importance of low-mode internal wave energy losses in this abyssal setting. Targeted and sustained observations near the seafloor at gateway regions of abyssal pathways are vital for understanding energy exchange that influences meridional overturning circulation. Our results highlight a regime where sustained low-mode internal tide energy loss, modulated by topographic slope and depth, governs the BML thickness in the abyssal Pacific. However, the rate at which BML thickness changes over time and the processes that cause these changes remain key unresolved factors.

Submarine landslides along the flanks of Christmas Island, Indian Ocean - Yakufu Niyazi; Heather A. Stewart; Devin Harrison; Alan J. Jamieson; Todd Bond (Geo-Marine Letters, 2025)
A variety of geological processes shape and modify the morphology of volcanic islands over a range of temporal timeframes. Amongst the most conspicuous are aerial and submarine landslides that are frequently observed in both island arc and intra-plate volcanic settings. Identifying and understanding the triggering mechanisms of these landslides is crucial to geohazard mitigation as they pose major threats to coastal communities as well as critical onshore and submarine infrastructure. Christmas Island, located in the northeast Indian Ocean rises steeply, more than 5000 m, from the surrounding ocean floor. In this study, we compile a seamless bathymetric surface from a number of sources and systematically describe four large-scale submarine landslides for the first time, with a combined areal coverage of 1711 km 2 , and numerous smaller mass-movements covering 339 km 2 . Based on their geomorphic characteristics observed from the high-resolution bathymetry data, two of the identified landslides can be classified as volcanic debris avalanches and the remainder as slumps. The distribution of landslides and planform orientation of the remnant headlands suggest the presence of volcanic rift zones that may have controlled the location of large landslides and the present-day shape of the island. In addition, we postulate that many of the major landslides formed prior to the emergence of the island as evidenced by relatively undisturbed onshore terraces interpreted as paleo-shorelines. Whilst the smaller slumps are likely triggered by subsequent volcanic eruptions and seismic activity associated with subduction at the adjacent Sunda Trench.

Opportunities to better integrate inland fish and fisheries in multilateral environmental agreements - Abigail J. Lynch; Devin Bartley; T. Douglas Beard, Jr.; Gabriel Borba; Steven J. Cooke; Ian G. Cowx; Vittoria Elliott; Holly Embke; Edith Gondwe; Zeb Hogan; Jonathan G. Low; Jamie C. Madden; et al. (Environmental Science & Policy, 2025)

Geophysical reconstruction of the late Holocene proximal proglacial landsystem at Skeiðarársandur, southeast Iceland - Devin Harrison; Neil Ross; Andrew J. Russell; Stuart J. Jones (Journal of Quaternary Science, 2023)
Sandur plains are extensive sedimentary bodies formed in proglacial settings by glaciofluvial processes. Icelandic sandar have been hypothesised to be comprised of thick alluvial successions that provide critical insight into the processes that contributed to their formation and evolution. However, to‐date, most sandar research has focused on the analysis of sedimentary successions associated to topographically‐confined and small‐scale systems. These, however, do not capture the variety or scale of processes that influence sandar architecture. Therefore, detailed subsurface analysis of large‐scale and unconfined sandar is vital to understand how these systems respond to fundamental drivers, such as: (i) glacier oscillations, and (ii) episodic sediment flux from glacier outburst floods (aka. jökulhlaups). We report an extensive, low‐frequency (40 & 100 MHz) ground‐penetrating radar (GPR) survey of the ice‐proximal component of a large‐scale () active sandur in southeast Iceland. A bright and continuous reflection (PR1) is identified within all radargrams and provides a boundary between pre‐LIA and LIA to present‐day sedimentation. GPR data reveals a ~50 m thick ice‐proximal sediment wedge that is attributed to jökulhlaup and surge‐related glaciofluvial activity during the Little Ice Age (LIA). An approximate rate of deposition of 0.2–0.65 m has been calculated for the sediment wedge above PR1. Furthermore, we propose an extensive, sandur‐wide, pre‐LIA ice marginal limit of Skeiðarárökull, southeast Iceland, based on observations reported here and in previous work.